“Assessment of the residual service life of wheeled motor units: methods, problems and prospects” (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article analyzes existing scientific approaches to assessing the residual life of wheel motor blocks, including statistical, diagnostic, modeling, and artificial intelligence-based methods. The advantages of each method are examined alongside their practical limitations. The author provides recommendations for implementing hybrid approaches, multi-parameter assessment systems, and the development of practical data bases tailored to the operational conditions in Uzbekistan. The article aims to improve the efficiency of technical maintenance, enable early fault detection, and ensure the operational reliability of motor blocks.